Interactive Game Media Development Wordwall Website Based on Class V Elementary School Science Lessons (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
This research was motivated by the low critical thinking skills of students in science learning. This study aims to This research aims to develop a learning media in the form of an interactive game using the Wordwall platform which is accessed via the website for Natural Sciences (Science) subjects at the Class V Elementary School level. The focus of the research lies in two initial stages, namely analysis and design. The analysis stage involves identifying student learning needs, collecting data related to the science curriculum, as well as evaluating effective learning methods for understanding grade V science material. From this analysis, the main objective is to ensure that the interactive games developed are in accordance with the applicable curriculum and meet needs. student learning. The design stage is related to detailed planning for the development of the interactive game. Selection of game type, material content presented, interactivity, and user interface are the main focus at this stage. This design is aimed at optimizing students' learning experiences and ensuring that the game can provide a deep understanding of class V science concepts. Although this research only reached the analysis and design stage, these steps are an important foundation for further development. It is hoped that in-depth analysis and well-planned design can make a significant contribution to the development of this interactive game media in supporting the science learning process for fifth grade elementary school students. The implementation, development and evaluation stages will be the next steps which are expected to produce useful and effective learning media.